Analisis Motilitas Dan Morfologi Spermatozoa Pria perokok Usia 18-24 tahun - yosha putri wahyuni (Faculty of Medicine, Universitas Andalas, 2023)
Background: Smoking is one of lifestyle factors which lead to health problems in society. Smoke can decrease the quality of spermatozoa by various mechanisms, one of which is the seminal oxidative stress induced by Reactive Oxygen Species (ROS). Excessive levels of ROS lead to the lipid peroxidation and the changes in sperm membrane function resulting to the decreased of sperm morphology, sperm motility and fertility.Objective: The purpose of this research is to determine the effect of smoking activity to sperm motility and morphology in men adult at the age between 18 and 24.Methods: This research was analytic research conducted using a cross sectional design. This study selected 52 males using a purposive random sampling technique. The examination of sperm motility and morphology was conducted using a microscope by counting 100 sperms.Results: The result showed that there was a difference of sperm motility between men who are smokers and non-smokers (p<0,05). However, there were not a significance difference of sperm morphology between men smokers and non-smokers at p>0,05.Conclusion: The research concluded that a smoking activity can influence men sperm motility but not the morphology of the samples of this study.